Statins and diabetes mellitus: risks and benefits - O. M. Drapkina; O. N. Korneeva; A. F. Sheptulina (Кардиоваскулярная терапия и профилактика)
Patients with diabetes mellitus (DM) are at a high risk of cardiovascular events (CVE). Currently, the predominant clinical strategy of the CVE prevention in DM patients is aggressive lowering of low-density lipoprotein cholesterol and blood pressure levels. In this clinical group, statins are among the most widely used pharmacological agents. Recent clinical evidence suggests that statin therapy could be associated with an increased risk of DM. Both clinicians and researchers need to reevaluate the issue of statin safety in the patients at a higher CVE risk. This review focuses on the problem of DM development in statin-treated patients.